Referral Incentives in Crowdfunding - Naroditskiy, Victor; Stein, Sebastian; Tonin, Mirco; Tran-Thanh, Long; Vlassopoulos, Michael; Jennings, Nicholas (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2014)
Word-of-mouth, referral, or viral marketing is a highly sought-after way of advertising. In this paper, we investigate whether such marketing can be encouraged through incentive mechanisms, thus allowing an organisation to effectively crowdsource their marketing. Specifically, we undertake a field experiment that compares several mechanisms for incentivising social media shares in support of a charitable cause. Our experiment takes place on a website promoting a fundraising drive by a large cancer research charity. Site visitors who sign up to support the cause are asked to spread the word about it on Facebook, Twitter or other channels. They are randomly assigned to one of four treatments that differ in the way social sharing activities are incentivised. Under the control treatment, no extra incentive is provided. Under two of the other mechanisms, the sharers are offered a fixed number of points that help take the campaign further. We compare low and high levels of such incentives for direct referrals. In the final treatment, we adopt a multi-level incentive mechanism that rewards direct as well as indirect referrals (where referred contacts refer others). We find that providing a high level of incentives results in a statistically significant increase in sharing behaviour and resulting signups. Our data does not indicate a statistically significant increase for the low and multi-level incentive mechanisms.